2017
DOI: 10.1155/2017/1323985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the BCI Performance between the Semitransparent Face Pattern and the Traditional Face Pattern

Abstract: Brain-computer interface (BCI) systems allow users to communicate with the external world by recognizing the brain activity without the assistance of the peripheral motor nervous system. P300-based BCI is one of the most common used BCI systems that can obtain high classification accuracy and information transfer rate (ITR). Face stimuli can result in large event-related potentials and improve the performance of P300-based BCI. However, previous studies on face stimuli focused mainly on the effect of various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Jin and his colleagues reported on a new emotion-detecting BCI system that employs a face-based image-induced paradigm (Cheng et al, 2017 ). In another study, Thammasan et al studied a continuous music-emotion-recognition approach for the construction of affective BCI (Thammasan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jin and his colleagues reported on a new emotion-detecting BCI system that employs a face-based image-induced paradigm (Cheng et al, 2017 ). In another study, Thammasan et al studied a continuous music-emotion-recognition approach for the construction of affective BCI (Thammasan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have indicated that, when familiar faces are used as stimuli, they may strongly elicit several ERPs, including the VPP, N200, P300, and N400 components. Cheng et al (2017) reported that the semitransparent face pattern can evoke larger N200 components, which can contribute to improving classification accuracy. Eimer (2000) revealed that familiar faces could elicit an N400 in parietal and central cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…A study that compared the face speller to a conventional matrix speller and another speller approach found that the face speller was most effective for participants with ALS, due largely to early ERP components (Geronimo & Simmons, 2017). Other reports described potential improvements to the face speller, such as semi‐transparent faces, familiar faces, moving faces, and presenting a new face image with each flash (Cheng, Jin, & Wang, 2017; Jin et al, 2012; Jin, Allison, Zhang, Wang, & Cichocki, 2014; Kaufmann, Schulz, et al, 2013; Yeom, Fazli, Müller, & Lee, 2014). Some work has focused on improving usability with face spellers.…”
Section: Seminal Studiesmentioning
confidence: 99%